Determinants of Derivative Usage and Firm Value Premium: An Empirical Analysis of UK Non-Financial Companies - Chen, Anqi (2018)
This study uses hedging information collected from annual reports of over 400 non-financial companies in UK from 2016 to 2017 to conduct an empirical research and try to figure out why and how UK firms hedge during this period. Both univariate and multivariate logit models are employed and the result shows that companies’ derivative usage largely depends on firm size, foreign currency exposure and floating debt proportion. Larger firms with higher foreign currency exposure are more likely to hedge using derivative but firms with more floating debt are less likely to use derivatives. This is consistent with findings from previous researches and the hypothesis that scale economics links to higher likelihood of hedging. Next, this paper applies fixed effect model to testify the effect of derivatives hedging on firm’s valuation. According to the result, there is no evidence showing that hedging with derivatives can increase firm value. Using commodity price derivative will even significantly decrease firm value. In the robustness test, industry factor is taken into concerned and used to adjust the dependent variable firm value. Result suggests that the model is robust and reliable. The insignificant or even negative impact of derivative usage on can be due to potential agency cost or the fact that derivative hedging reduces information asymmetries so the market price would approach intrinsic value.